Face Negotiation Approaches in the Sulalatus Salatin Text - Jaffar, Siti Rabiatul Adawiah; Sarji, Kasmaizun Enuni; Huszka, Balazs; Zain, Rosnani (Malay Literature, 2025)
This study analyses ways of managing face (air muka) in the classical Sulalatus Salatin text using Ting-Toomey’s (1988) face negotiation theory framework. The concept of face, which encompasses honour, self-worth, and reputation, is an essential aspect of Malay society’s communication culture, which is based on civility and social harmony. Although this theory has been applied cross-culturally and in modern communication contexts, its application to the reading of classical texts is underexplored. The main objective of this study is to analyse the forms and styles of face management employed by the characters in Sulalatus Salatin, based on the framework of face negotiation theory, through 12 key events involving conflicts of dignity and feelings of shame. Four approaches to face negotiation have been identified, namely face-restoration, face-assertion, face-saving, and face-giving. The findings show face-assertion to be the most dominant mode, which reflects the characters’ efforts to guard their honour in the context of a collectivist culture. This study indicates that modern communication theories can be effectively applied in the examination of traditional discourse, which simultaneously opens up interdisciplinary spaces between literary and cultural communication studies. These findings also strengthen our understanding of classical Malay value systems in managing conflict and sustaining social harmony.  Keywords : Sulalatus Salatin, face, incidents of embarrassment, face negotiation theory, Malay culture, intercultural communication Full text:   PDF